2020
DOI: 10.1088/1475-7516/2020/09/047
|View full text |Cite
|
Sign up to set email alerts
|

How attractive is the isotropic attractor solution of axion-SU(2) inflation?

Abstract: The key to the phenomenological success of inflation models with axion and SU(2) gauge fields is the isotropic background of the SU(2) field. Previous studies showed that this isotropic background is an attractor solution during inflation starting from anisotropic (Bianchi type I) spacetime; however, not all possible initial anisotropic parameter space was explored. In this paper, we explore more generic initial conditions without assuming the initial slow-roll dynamics. We find some initial anisotropic parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Consequently, we see the entire phase space converges to the FLRW metric. The area previously failing to converge (the white region in the left panel) [1] coincides with the region in which β changes signs during the evolution. This plot shows the system studied in [1] with the parameters given in table 2.…”
Section: Parametermentioning
confidence: 73%
See 3 more Smart Citations
“…Consequently, we see the entire phase space converges to the FLRW metric. The area previously failing to converge (the white region in the left panel) [1] coincides with the region in which β changes signs during the evolution. This plot shows the system studied in [1] with the parameters given in table 2.…”
Section: Parametermentioning
confidence: 73%
“…The aim of this paper was to study this system with a different parametrization to investigate the nature of the no-go area in detail. We found that the numerical breakdown observed in [1] was an artifact of performing the numerical analysis based on the (ψ, β) parametrization, which is not well-defined at β = 0 and unstable at β → ±∞. This is problematic in the no-go area, i.e., large gauge field's kinetic term, in which the β(t) field switches sign during its evolution.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Ref. [26], the classical isotropisation of inflating space times in the presence of SU(2)-gauge fields coupled with an axion was also studied, and it was shown that some initial configurations lead to a premature termination of slow-roll inflation if the axion drives inflation. In Ref.…”
Section: Discussionmentioning
confidence: 99%